Development of an integrated fermentation pervaporation model for bioethanol production - Hamid, Zentou (2021)
The continuous fermentation process where ethanol is selectively removed from the broth is an efficient technique for optimising the bioethanol productivity and limiting the inhibitory effect of both end product and substrate. However, the application of this approach may increase the concentration of minor secondary products to the point where they become toxic to the yeast. Despite that several studies have reported the significant inhibitory effect of byproducts, there is currently no fermentation model that considers the inhibitory effect of these byproducts. In this study, an integrated model of a fermentation-pervaporation system was developed considering the effect of the interaction between both processes with special attention has been devoted to the inhibitory effect of byproducts. Firstly, a modified Monod model for the alcoholic fermentation process was developed. Then, the optimization and modelling of the pervaporation process for ethanol recovery were conducted. Finally, the integrated model of alcoholic fermentation coupled with a pervaporation system for ethanol recovery was developed and validated. The findings showed that glycerol, acetic acid and succinic acid were the main byproducts during the fermentation process. It was also noted that the concentration of these byproducts linearly increased with the increase of glucose concentration in the range of 25-250 g/L. A modified Monod model concerning the inhibitory effect of these byproducts was suggested where the specific growth coefficient exponentially decreased with the increase of byproducts concentration in the fermentation broth. The suggested model showed a good agreement with the experimental data and higher accuracy compared to the conventional Monod model. In optimization of the pervaporation process, the ethanol feed concentration and the permeate pressure positively affected the selectivity, while the feed temperature and the feed flow rate showed a negative effect. The results also revealed that all the four studied factors had a positive effect on the total flux in the selected range. In addition, A solution-diffusion model has been developed and validated using the fermentation broth as a feed solution where it showed high accuracy with R2 higher than 0.96 for predicting the permeate total flux. A full model was developed by the integration of the modified Monod model and the solution-diffusion model of the pervaporation process considering the interactions between both processes. The suggested model could accurately predict the biomass concentration, glucose concentration, and ethanol concentration in the fermentation broth simultaneously with predicting the total permeate flux, ethanol flux, and water flux in the collected permeate during a long-term continuous fermentation.